2019
DOI: 10.1109/tie.2018.2860567
|View full text |Cite
|
Sign up to set email alerts
|

Fast Estimation of Phase and Frequency for Single-Phase Grid Signal

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…The voltage sag effect didn't show any change in the time delay adjustment as the deviation in frequency settled to less 0.5Hz in less than one cycle (0.02 sec). The results were also benchmarked against results obtained in [18] to verify the efficiency and accuracy of the proposed technique. Table 1 summaries the steady state performance as obtained from the proposed MTDPLL and from SOGI-FLL and AO methods.…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The voltage sag effect didn't show any change in the time delay adjustment as the deviation in frequency settled to less 0.5Hz in less than one cycle (0.02 sec). The results were also benchmarked against results obtained in [18] to verify the efficiency and accuracy of the proposed technique. Table 1 summaries the steady state performance as obtained from the proposed MTDPLL and from SOGI-FLL and AO methods.…”
Section: Results and Analysismentioning
confidence: 99%
“…The results in Table 1 showed that the proposed MTDPLL produced a comparable performance in terms of steady state error and settling time given the simplicity of the proposed technique. [18] Finally, the effect of low order harmonic distortion is examined. Figure 11 shows the harmonic content in the grid signal that has been used in this part of the simulation.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations